2014
DOI: 10.3758/s13414-013-0602-2
|View full text |Cite
|
Sign up to set email alerts
|

Duration perception of visual and auditory oddball stimuli: Does judgment task modulate the temporal oddball effect?

Abstract: The duration of rare stimuli (oddballs) presented within a stream of homogenous standards tends to be overestimated. This temporal oddball effect (OE) has been attributed to perceptual processes. The OE is usually assessed with a comparative judgment task. It has been argued, however, that this task is prone to decision biases. The present experiments employed comparative and equality judgments, since it has been suggested that equality judgments are less vulnerable to such biases. Experiments 1a and 1b used v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 45 publications
5
58
1
Order By: Relevance
“…Tse et al observed overestimations of the oddballs' duration in the order of 35 %. This basic effect has not only been observed for expanding disks but also for stationary oddballs which only deviated from the standards in shape or color (Birngruber et al 2014a;Chen and Yeh 2009;Schindel et al 2011).…”
Section: Abstract Time Perception · Oddball Effect · Stimulus Frequencymentioning
confidence: 90%
See 3 more Smart Citations
“…Tse et al observed overestimations of the oddballs' duration in the order of 35 %. This basic effect has not only been observed for expanding disks but also for stationary oddballs which only deviated from the standards in shape or color (Birngruber et al 2014a;Chen and Yeh 2009;Schindel et al 2011).…”
Section: Abstract Time Perception · Oddball Effect · Stimulus Frequencymentioning
confidence: 90%
“…Tse et al observed overestimations of the oddballs' duration in the order of 35 %. This basic effect has not only been observed for expanding disks but also for stationary oddballs which only deviated from the standards in shape or color (Birngruber et al 2014a;Chen and Yeh 2009;Schindel et al 2011).However, follow-up studies have usually reported distinctly smaller OEs than those reported by Tse et al (2004). In their original study, Tse et al employed comparison durations that were mostly shorter than the standard duration.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, based on his research on pitch and loudness discrimination, Doughty (1949) concluded that this method should not be used for assessing the PSE or the constant error (i.e., standard minus PSE) even though it may be suited to determine the difference threshold. However, the method of constant stimuli has been successfully used to investigate temporal phenomena related to perceived duration, for example, in studies on intentional binding (Nolden, Haering, & Kiesel, 2012), the temporal oddball effect (Birngruber, Schröter, & Ulrich, 2014;Tse, Intriligator, Rivest, & Cavanagh, 2004), the effects of stimulus repetition (Matthews, 2011), or the influence of global temporal contexts (Jones & McAuley, 2005). All these studies used comparison intervals that were symmetrically distributed around the physical standard duration, thereby avoiding a possible asymmetry effect.…”
Section: Discussionmentioning
confidence: 99%